Teacher Professional Development Strategies through Effective Management - Yusron, Ali; Nurjanah; Priyantoro, Dian Eka (Gestion Educativa, 2025)
This study aims to analyze teacher professional development strategies that are integrated in effective school management practices. The background of this research is based on the importance of improving teachers' competence in facing the demands of the Independent Curriculum and the development of education in the era of the Industrial Revolution 4.0 and Society 5.0. Although various development programs have been carried out, there are still limitations in terms of sustainability, relevance, and integration between teacher development and school management systems. This study uses a qualitative approach with a case study design. The informants consist of school principals, teachers, and managerial staff in the primary education unit who are selected purposively. Data collection techniques include in-depth interviews, direct observation, and document analysis related to the planning and implementation of teacher professional development. Data is analyzed by data reduction techniques, data presentation, and conclusion drawn. The results of the study show that teachers' professional development strategies are designed in a participatory and needs-based manner, implemented through various collaborative methods such as internal training, learning communities, lesson studies, and peer coaching, and supervised through academic supervision and continuous program evaluation. Factors supporting the success of this strategy include principals' leadership, collaborative culture, and budget support, while the obstacles include time constraints and resistance to change. From these results, it is concluded that the effectiveness of school management plays an important role in creating a learning ecosystem that supports the professional development of teachers in a sustainable manner. These findings provide conceptual and practical contributions for school principals, policy makers, and related parties in designing more strategic and contextual teacher quality improvement strategies.